Effect of Clinical Decision Support System on Dose Adjustments in Inpatients with Renal Failure at Thai Binh Medical University Hospital - Thanh Hai, Nguyen; Nguyet Ha, Dang; Trong Hieu, Le; Thi Cat Khanh, Tran; Viet Khanh, Nguyen; Than Binh, Vu; Thi Thu Thuy, Tran; Xuan Bach, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 1, 2024)
Objective: The study aimed to evaluate the effectiveness of the Clinical Decision Support System (CDSS) in dosage adjustment for inpatients with renal impairment at Thai Binh University Hospital. Subjects and methods: Medical records of inpatients treated at Thai Binh University Hospital were reviewed during the periods from 01/01/2022 to 30/11/2022 and from 01/12/2022 to 15/03/2023. Study design: a cross-sectional descriptive study. Results: Before the integration of CDSS, among 300 medical records, dose adjustment was required in 81.7% of medical records, which included 64.5% inappropriate dosage modification. There were 406 prescriptions requiring dose adjustment, accounting for 31.5% of the total prescriptions, and 52.7% of the total prescriptions had inappropriate dose adjustment. After the integration of CDSS, 320 alerts were recorded for 55 patients between December 1 st , 2022, and March 15 th , 2023. The alert cancellation proportion was 2.8%. Among the alerts that were overridden, 55.6% involved clinical pharmacist consultations. The combination of CDSS and clinical pharmacist consultations reduced the proportion of prescriptions and medical records having inappropriate dosage adjustments to 10.6% and 16.4%, respectively. Conclusion: CDSS had positive impacts on dosage adjustments in inpatients with renal insufficiency at Thai Binh Medical University Hospital.